THE INFLUENCE OF UTILITARIAN BENEFITS, SEXUAL ATTRACTIVENESS, AND SOCIAL INTERACTION SUCCESS ON SELF-ESTEEM (A Study on Beauty Clinic Users) - I Gusti Ayu Wina Fridayanti; Agung Artha Kusuma (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The transformation of beauty standards has increased individuals’ awareness of the importance of physical appearance. Beauty treatments are no longer perceived solely as efforts to enhance physical appearance but also as a means of improving psychological aspects, particularly self-esteem. Beauty standards today, largely shaped by social media, encourage individuals to engage in aesthetic treatments in order to obtain functional benefits, enhance perceived attractiveness, and achieve greater social acceptance. However, research examining the psychological dimensions of aesthetic service consumers remains relatively limited. Therefore, this study aims to analyze the influence of utilitarian benefits, sexual attractiveness, and social interaction success on self-esteem among beauty clinic consumers in Denpasar City. This research employed a quantitative approach with an associative design, involving 140 respondents selected through purposive sampling. The results indicate that utilitarian benefits, sexual attractiveness, and social interaction success have a positive and significant effect on self-esteem, with sexual attractiveness emerging as the most dominant variable. The research model explains 40.9% of the variance in self-esteem. This study provides theoretical contributions by extending consumer behavior research into the psychological domain and offers practical implications for beauty clinic managers in designing services that align with customers’ psychological needs. Keywords: utilitarian benefits; sexual attractiveness; social interaction success; self-esteem; beauty clinic